Vibration Damage Near Dwellings in Overland Park, Kansas - D G. Dressler; Paul Yeager (International Society of Explosives Engineers, 1987)
A previously little-known facet of seismic frequency spectrum analysis is gaining significance. The frequency spectrum of seismic waves promulgated from blasting is a significant factor in causing blasting complaints and threshold (architectural type) damages.